High-strength palladium-based hydrogen permeation material as well as preparation method and application thereof
By preparing PdSc alloys with high tensile and compressive strength, the problem of insufficient strength of palladium-based hydrogen permeable materials is solved, and more efficient hydrogen transmittance and rate is achieved, product life is extended, and the resistance of thin-walled tubes is improved. Pressure strength.
Patent Information
- Application Number
- CN202411436922.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-14
AI Technical Summary
The existing palladium-based hydrogen permeable materials are insufficient in the preparation process of high-purity hydrogen, resulting in the product being easily deformed and damaged, and the hydrogen pressure limits the hydrogen permeability efficiency.
Prepare PdSc alloys with high tensile strength and compressive strength, and manufacture high-strength palladium-based hydrogen permeable materials through vacuum smelting, casting and homogenizing heat treatment. They are used to make foils and thin-walled tubes with smaller thicknesses, increasing hydrogen pressure to enhance permeability. Hydrogen effect.
It improves the strength and hydrogen permeability efficiency of hydrogen permeability materials, extends the product life, enhances the compressive strength of thin-walled tubes, and improves the hydrogen permeability and rate.
Smart Images

Figure BDA0005085282460000071 
Figure BDA0005085282460000081 
Figure BDA0005085282460000082
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogen purification and relates to a high-strength palladium-based hydrogen permeable material and a preparation method and application thereof. Background Art
[0002] Hydrogen permeation technology is commonly used in the preparation of high-purity hydrogen in the fields of nuclear energy and new energy. In the preparation of high-purity hydrogen, materials are usually made into two products, foil and thin-walled tube, for hydrogen permeation. The precious metal element palladium (Pd) has the characteristics of permeating hydrogen and purifying it, but the hydrogen permeation effect of pure palladium is poor. At the same time, after absorbing hydrogen, it will produce a large deformation, resulting in the inability of products made of pure palladium to meet the hydrogen permeation requirements in the preparation of high-purity hydrogen. The product is easily deformed and damaged, and has a short service life.
[0003] At present, Pd and yttrium (Y) alloy or Pd and silver (Ag) alloy is usually used to make hydrogen permeable products for use in the high-purity hydrogen preparation process. However, due to the limitation of alloy strength performance, the thickness of existing foil hydrogen permeable products can only reach 0.05-0.08 mm, and the wall thickness of thin-walled tubes can also only reach 0.05-0.08 mm. At the same time, during the use of thin-walled tubes, in order to ensure that the thin-walled tubes do not break or damage, the hydrogen pressure usually needs to be controlled below 0.8 MPa, which has a certain limitation on the hydrogen permeability efficiency.
[0004] Therefore, it is necessary to provide a high-strength palladium-based hydrogen permeable material and a preparation method thereof to improve the strength performance of the alloy, thereby improving the hydrogen permeability effect of the alloy after being made into a specific product. Summary of the invention
[0005] In order to overcome the problems in the background technology, the present invention prepares a PdSc alloy with high tensile strength and compressive strength. When the PdSc alloy is used to make a foil product or a thin-walled tube product, due to the high tensile strength and compressive strength of the alloy, a foil product with a smaller thickness and a thin-walled tube product with a smaller wall thickness can be produced. At the same time, during the use of the thin-walled tube, the hydrogen pressure can be increased without damaging the thin-walled tube. The thickness of the foil product and the thickness of the thin-walled tube product are smaller, which is conducive to improving the hydrogen permeability. At the same time, increasing the hydrogen pressure can increase the rate at which hydrogen permeates the hydrogen permeable product, thereby comprehensively improving the hydrogen permeability effect of the product.
[0006] In order to achieve the above object, the present invention is implemented by the following technical solutions:
[0007] In one aspect, the present invention provides a high-strength palladium-based hydrogen permeable material. The chemical composition of the high-strength palladium-based hydrogen permeable material includes, by weight, Sc: 1% to 15%, Sm≤8%, and the remainder is Pd.
[0008] Another aspect of the present invention provides a method for preparing the above-mentioned high-strength palladium-based hydrogen permeable material, the preparation method comprising the following steps:
[0009] The preparation method comprises the following steps:
[0010] (1) Melting: adding raw materials into a crucible and performing vacuum melting to obtain molten metal;
[0011] (2) Casting: casting the molten metal obtained in step (1) into a steel mold to obtain an alloy ingot;
[0012] (3) Homogenization heat treatment: The alloy ingot obtained in step (2) is tightly wrapped with nickel foil, and then the alloy ingot is subjected to homogenization heat treatment. After the heat treatment is completed, water quenching is performed to obtain a palladium-based hydrogen permeable material.
[0013] Preferably, in the raw materials, the purity of Pd is not less than 99.99%, the purity of Sc is not less than 99.9%, and the purity of Sm is not less than 99.9%.
[0014] Preferably, in step (1), the vacuum melting temperature is 1550-1600°C, the melting time is 20 min, the melting frequency is 50 KHz, and the background vacuum degree is ≥10 -3 Pa.
[0015] Preferably, in step (1), the crucible is made of one of corundum, zirconium oxide and magnesium oxide.
[0016] Preferably, in the step (1), vacuum arc flip melting is performed before vacuum melting.
[0017] Preferably, in the vacuum arc flipping melting process, the melting temperature is 1550-1600° C., the melting time is 20 min, and the flipping times are 3 times.
[0018] Preferably, in the step (2), the steel mold is heated to not less than 300° C. before casting.
[0019] Preferably, in step (3), the heat treatment temperature is 1000-1100° C., and the heat treatment time is 4-4.5 h.
[0020] The present invention also proposes the use of the high-strength palladium-based hydrogen permeable material in the manufacture of hydrogen permeable foil or hydrogen permeable thin-walled tube products, and uses the high-strength palladium-based hydrogen permeable material as a raw material to manufacture hydrogen permeable foil or hydrogen permeable thin-walled tube.
[0021] Beneficial effects of the present invention:
[0022] 1. The present invention improves the strength of palladium-based hydrogen permeable materials, thereby providing support for reducing the thickness of hydrogen permeable foil and hydrogen permeable thin-walled tubes and improving the compressive strength of thin-walled tubes, thereby simultaneously improving the hydrogen permeability and hydrogen permeability rate during the actual hydrogen permeation process, and ultimately improving the hydrogen permeation effect of hydrogen permeable products.
[0023] 2. The present invention performs vacuum arc flip melting before vacuum melting to make the composition of the alloy ingot more uniform, thereby further enhancing the strength performance of the alloy.
[0024] 3. The present invention heats the steel mold to not less than 300° C. before casting, which is beneficial to reducing the fiber looseness defect of the ingot. DETAILED DESCRIPTION
[0025] The present invention is further described in detail below in conjunction with specific embodiments.
[0026] Example 1
[0027] In this embodiment, PdSc alloy is prepared by the following method:
[0028] 198 g of Pd sheets with a purity of 99.99% and 2 g of Sc particles with a purity of 99.9% were weighed to prepare a PdSc alloy raw material with a Sc weight fraction of 1%.
[0029] Add all the weighed alloy raw materials into the corundum crucible, and put the corundum crucible into the vacuum melting furnace. Evacuate the vacuum melting furnace to make the ambient vacuum degree reach at least 10 -3 Pa, in a vacuum environment, heat the alloy raw material to 1550℃, and melt it at a melting frequency of 50KHz. After melting for 20 minutes, take out the corundum crucible, and pour the molten metal into the steel mold. Before pouring the molten metal into the steel mold, heat the steel mold to 300℃. After casting, a cylindrical ingot with a diameter of 17mm is obtained. Before vacuum melting, according to actual conditions, the alloy raw material can be first added to the corundum crucible, and the alloy raw material can be turned over and melted at 1550-1600℃ using a non-consumable vacuum arc melting furnace for 20 minutes. During the melting process, it is turned over 3 times.
[0030] The cylindrical ingot is tightly wrapped with nickel foil, and the ingot wrapped with nickel foil is placed in a muffle furnace, and the ingot is kept warm for 4 hours at 1000°C for homogenization heat treatment. After the heat treatment, the ingot is taken out of the furnace and water quenched to obtain a PdSc hydrogen permeable material, which is recorded as Pd1Sc in this embodiment. At the same time, after the homogenization heat treatment, the shape and size of the Pd1Sc hydrogen permeable material will not change.
[0031] In this embodiment, Pd1Sc hydrogen permeable material is used as raw material, and the foil is prepared by the following method:
[0032] First, the Pd1Sc hydrogen permeable material is rolled by a two-roll mill or a four-roll mill, the deformation per pass is not more than 15%, and the total deformation is not more than 50%. After one rolling, the rolled sample is annealed at 900°C for 5-40 minutes. The specific annealing time is determined according to the thickness of the sample after this rolling. After the annealing, the annealed sample is quenched. After quenching, the quenched sample is continued to be rolled to reduce the sample thickness again. After each rolling, annealing and quenching are performed, and this cycle is repeated until a foil with a thickness of 0.06 mm is obtained. Finally, the foil is heat treated at 750°C for 40 minutes to further improve the hydrogen permeability of the foil.
[0033] Example 2
[0034] This embodiment adopts the same method as that of Embodiment 1 to produce foil of the same thickness, except that: in this embodiment, 190 g of Pd sheet and 10 g of Sc particles are weighed, and the weight fraction of Sc is 5%. In this embodiment, the vacuum melting temperature is 1570°C, the homogenization heat treatment temperature is 1050°C, the holding time is 4.2 h, and the rolling annealing temperature is 950°C.
[0035] The hydrogen permeable material in this embodiment is recorded as Pd5Sc.
[0036] Example 3
[0037] This embodiment adopts the same method as that of Embodiment 1 to produce foil of the same thickness, except that: in this embodiment, 184 g of Pd sheet and 16 g of Sc particles are weighed, and the weight fraction of Sc is 8%. In this embodiment, the vacuum melting temperature is 1600°C, the homogenization heat treatment temperature is 1100°C, the holding time is 4.5 h, and the rolling annealing temperature is 1000°C.
[0038] The hydrogen permeable material in this embodiment is recorded as Pd8Sc.
[0039] Example 4
[0040] This embodiment adopts the same method as that of embodiment 1 to prepare foil with the same thickness, except that: in this embodiment, 180 grams of Pd sheets and 20 grams of Sc particles are weighed, and the weight fraction of Sc is 10%.
[0041] The hydrogen permeable material in this embodiment is recorded as Pd10Sc.
[0042] Example 5
[0043] This embodiment adopts the same method as that of embodiment 1 to prepare foil with the same thickness, except that: in this embodiment, 170 g of Pd sheet and 30 g of Sc particles are weighed, and the weight fraction of Sc is 15%.
[0044] The hydrogen permeable material in this embodiment is recorded as Pd15Sc.
[0045] Example 6
[0046] This embodiment adopts the same method as that of Embodiment 1 to produce foil with the same thickness, except that: in this embodiment, 180 grams of Pd sheet, 16 grams of Sc particles, and 4 grams of Sm particles are weighed, the weight fraction of Sc is 8%, and the weight fraction of Sm is 2%.
[0047] The hydrogen permeable material in this embodiment is recorded as Pd8Sc2Sm.
[0048] Example 7
[0049] This embodiment adopts the same method as that of Embodiment 1 to produce foil with the same thickness, except that: in this embodiment, 176 grams of Pd sheet, 16 grams of Sc particles, and 8 grams of Sm particles are weighed, the weight fraction of Sc is 8%, and the weight fraction of Sm is 4%.
[0050] The hydrogen permeable material in this embodiment is recorded as Pd8Sc4Sm.
[0051] Example 8
[0052] This embodiment adopts the same method as that of embodiment 1 to prepare Pd1Sc hydrogen permeable material. The shape and size of the Pd1Sc hydrogen permeable material are the same as those of embodiment 1. This embodiment uses Pd1Sc hydrogen permeable material to prepare a thin-walled tube by the following method:
[0053] First, the Pd1Sc hydrogen permeable material is punched to make a tube blank, and then the Pd1Sc hydrogen permeable material is rolled by a three-roll cold rolling mill, with a deformation of no more than 15% per pass and a total deformation of no more than 50%. After one rolling, the rolled sample is annealed at 900°C for 5-40 minutes. The specific annealing time is determined according to the wall thickness of the sample after this rolling. After annealing, the annealed sample is quenched. After quenching, the quenched sample is continued to be rolled to reduce the sample thickness again. After each rolling, annealing and quenching are performed, and this cycle is repeated until a tube sample with an outer diameter of 6 mm and a wall thickness of 0.5 mm is obtained. Then, a precision drawing machine is used to draw the tube sample to a tube with an outer diameter of 2 mm and a wall thickness of 0.08 mm. Finally, the tube is heat treated at 750°C for 40 minutes to further improve the hydrogen permeability of the tube.
[0054] Example 9
[0055] This embodiment adopts the same method as that of embodiment 8 to make a thin-walled tube with the same specifications, except that: in this embodiment, 190 g of Pd flakes and 10 g of Sc particles are weighed, and the weight fraction of Sc is 5%. In this embodiment, the vacuum melting temperature is 1570°C, the homogenization heat treatment temperature is 1050°C, the holding time is 4.2 h, and the rolling annealing temperature is 950°C. The tube is drawn to a wall thickness of 0.02 mm.
[0056] The hydrogen permeable material in this embodiment is recorded as Pd5Sc.
[0057] Example 10
[0058] This embodiment adopts the same method as that of Embodiment 8 to produce thin-walled tubes of the same specifications, with the difference that: in this embodiment, 184 grams of Pd sheets and 16 grams of Sc particles are weighed, and the weight fraction of Sc is 8%. In this embodiment, the vacuum melting temperature is 1600°C, the homogenization heat treatment temperature is 1100°C, the holding time is 4.5h, and the rolling annealing temperature is 1000°C.
[0059] The hydrogen permeable material in this embodiment is recorded as Pd8Sc.
[0060] Embodiment 11
[0061] This embodiment adopts the same method as that of Embodiment 8 to make a thin-walled tube, except that: in this embodiment, 184 grams of Pd sheets and 16 grams of Sc particles are weighed, and the weight fraction of Sc is 8%. In this embodiment, the tube is drawn to a wall thickness of 0.02 mm.
[0062] The hydrogen permeable material in this embodiment is recorded as Pd8Sc.
[0063] Example 12
[0064] This embodiment adopts the same method as that of Embodiment 8 to produce thin-walled tubes of the same specifications, with the difference that: in this embodiment, 180 grams of Pd sheets and 20 grams of Sc particles are weighed, and the weight fraction of Sc is 10%. In this embodiment, the tube is drawn to a wall thickness of 0.02 mm.
[0065] The hydrogen permeable material in this embodiment is recorded as Pd10Sc.
[0066] Embodiment 13
[0067] This embodiment adopts the same method as that of Embodiment 8 to produce thin-walled tubes of the same specifications, with the difference that: in this embodiment, 170 grams of Pd sheets and 30 grams of Sc particles are weighed, and the weight fraction of Sc is 15%. In this embodiment, the tube is drawn to a wall thickness of 0.02 mm.
[0068] The hydrogen permeable material in this embodiment is recorded as Pd15Sc.
[0069] Embodiment 14
[0070] This embodiment adopts the same method as that of Embodiment 8 to produce thin-walled tubes of the same specifications, with the difference that: in this embodiment, 180 grams of Pd sheets, 16 grams of Sc particles, and 4 grams of Sm particles are weighed, the weight fraction of Sc is 8%, and the weight fraction of Sm is 2%. In this embodiment, the tube is drawn to a wall thickness of 0.02 mm.
[0071] The hydrogen permeable material in this embodiment is recorded as Pd8Sc2Sm.
[0072] Embodiment 15
[0073] This embodiment adopts the same method as that of Embodiment 8 to produce thin-walled tubes of the same specifications, with the difference that: in this embodiment, 176 grams of Pd sheets and 16 grams of Sc particles are weighed, the weight fraction of Sc is 8%, and the weight fraction of Sm is 4%. In this embodiment, the tube is drawn to a wall thickness of 0.02 mm.
[0074] The hydrogen permeable material in this embodiment is recorded as Pd8Sc4Sm.
[0075] Comparative Example 1
[0076] This comparative example adopts the same method as Example 3 to prepare foil with the same specifications, except that: the alloy raw materials of this comparative example are 184 grams of Pd sheets with a purity of 99.99%, 16 grams of Y particles with a purity of 99.9%, and the weight fraction of Y is 8%.
[0077] The hydrogen permeable material in this comparative example is recorded as Pd8Y.
[0078] Comparative Example 2
[0079] This comparative example adopts the same method as Example 10 to make thin-walled tubes with the same specifications, except that: the alloy raw materials of this comparative example are 184 grams of Pd sheets with a purity of 99.99%, 16 grams of Y particles with a purity of 99.9%, and the weight fraction of Y is 8%.
[0080] The hydrogen permeable material in this comparative example is recorded as Pd8Y.
[0081] The hardness and tensile strength of the foils and tubes prepared in the examples and comparative examples were tested, and the results are shown in Table 1.
[0082] Table 1
[0083]
[0084]
[0085] Note: In Table 1, Φ represents the outer diameter of the pipe.
[0086] By comparing Example 3 with Comparative Example 1, it can be seen that the hardness of the foil of Example 3 is increased by 12.37% relative to that of Comparative Example 1, and the tensile strength is increased by 46.59%. Specifically, as the hardness increases, the compressive strength of the foil will also increase accordingly, thereby supporting the rolling of thinner foils.
[0087] By comparing Example 3 with Examples 6-7, and Example 11 with Examples 14-15, it can be seen that the addition of samarium (Sm) promotes the improvement of the hardness and tensile strength of the foil and the tube, among which the promotion effect on the improvement of the tensile strength is particularly obvious. The compressive and tensile strengths of the foil and the tube basically come from the high compressive and tensile strengths of the hydrogen permeable material, which can support the production of thinner foils and thinner wall tubes.
[0088] 100 pipes prepared in Example 10 and Comparative Example 2 were selected for pressure resistance test. The test used nitrogen pressurization and maintained the pressure for 1 hour. The results are shown in Table 2.
[0089] Table 2
[0090]
[0091] It can be seen from Table 2 that the pipe made of the hydrogen permeable material of the present invention exhibits more excellent compressive strength performance than the pipe made of the hydrogen permeable material of Comparative Example 2 under the same test conditions. Therefore, the pipe made of the hydrogen permeable material of the present invention can withstand a greater pressure without being damaged, and can withstand a greater hydrogen pressure during the hydrogen permeation process, thereby improving the hydrogen permeation rate.
[0092] Examples 10-12 and the pipe of comparative example 2 were selected to perform hydrogen permeability tests, and the results are shown in Table 3.
[0093] Table 3
[0094]
[0095] By comparing Example 10 with Comparative Example 2, it can be seen that the hydrogen permeable material of the present invention has almost no negative impact on the hydrogen permeability when improving the strength performance, and can maintain a good hydrogen permeability; by comparing Examples 11-12 with Example 10 and Comparative Example 2, it can be seen that the pipe with a thinner wall thickness has a better hydrogen permeability than the pipe with a thicker wall thickness. Therefore, the hydrogen permeable material of the present invention can support the production of a pipe with a thinner wall thickness, thereby improving the hydrogen permeability.
[0096] In summary, the strength performance of the hydrogen permeable material of the present invention is improved, thereby providing support for using the hydrogen permeable material of the present invention to make thinner foils and thinner wall thickness pipes with better compressive strength, and ultimately improving the hydrogen permeability effect of the hydrogen permeable foils and pipes used in the preparation process of high-purity hydrogen.
Claims
1. A high-strength palladium-based hydrogen permeable material, characterized in that: The chemical composition of the high-strength palladium-based hydrogen-permeable material includes, by weight percentage, Sc: 1% to 15%, Sm≤8%, and the remainder is Pd.
2. A method for preparing a high-strength palladium-based hydrogen permeable material according to claim 1, characterized in that: The preparation method comprises the following steps: (1) Melting: adding raw materials into a crucible and performing vacuum melting to obtain molten metal; (2) Casting: casting the molten metal obtained in step (1) into a steel mold to obtain an alloy ingot; (3) Homogenization heat treatment: The alloy ingot obtained in step (2) is tightly wrapped with nickel foil, and then the alloy ingot is subjected to homogenization heat treatment. After the heat treatment is completed, water quenching is performed to obtain a palladium-based hydrogen permeable material.
3. The preparation method according to claim 2, characterized in that: In the raw materials, the purity of Pd is not less than 99.99%, the purity of Sc is not less than 99.9%, and the purity of Sm is not less than 99.9%.
4. The preparation method according to claim 2, characterized in that: In the step (1), the vacuum melting temperature is 1550-1600°C, the melting time is 20 min, the melting frequency is 50 KHz, and the background vacuum degree is ≥10 -3 Pa.
5. The preparation method according to claim 2, characterized in that: In the step (1), the crucible is made of one of corundum, zirconium oxide and magnesium oxide.
6. The preparation method according to claim 2, characterized in that: In the step (1), vacuum arc flip melting is first performed before vacuum melting.
7. The preparation method according to claim 6, characterized in that: During the vacuum arc flipping melting process, the melting temperature is 1550-1600° C., the melting time is 20 minutes, and the flipping times are 3 times.
8. The preparation method according to claim 2, characterized in that: In the step (2), before casting, the steel mold is heated to not less than 300°C.
9. The preparation method according to claim 2, characterized in that: In the step (3), the heat treatment temperature is 1000-1100° C., and the heat treatment time is 4-4.5 hours.
10. Use of the high-strength palladium-based hydrogen permeable material according to claim 1 in the manufacture of hydrogen permeable foil or hydrogen permeable thin-walled tube products.